2004
DOI: 10.1046/j.1529-8817.2004.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the loricrin (LOR) gene as a positional candidate for the PSORS4 psoriasis susceptibility locus

Abstract: SummaryPsoriasis is a chronic inflammatory disease of the skin with both genetic and environmental risk factors. Nonparametric linkage analyses have mapped many susceptibility loci on different chromosomes. We mapped one of these loci, PSORS4, on human chromosome 1q21. Using the linkage disequilibrium approach, we refined the critical region to a specific genomic interval of about 100 Kb which contains only the loricrin (LOR) gene. Here we report a genetic and functional study of this gene to verify its involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 27 publications
3
26
0
1
Order By: Relevance
“…We failed to identify sequence disease-specific variants. However, we confirmed the existence of SNPs previously characterized [9] . We typed SNPs (rs943967; rs6661601; rs12136773) using allele/haplotype TDT analysis.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…We failed to identify sequence disease-specific variants. However, we confirmed the existence of SNPs previously characterized [9] . We typed SNPs (rs943967; rs6661601; rs12136773) using allele/haplotype TDT analysis.…”
Section: Resultssupporting
confidence: 89%
“…Locus overlapping was recently excluded for ATOD4 and PSORS2 on chromosome 17q25 [8] . Here, we report the results of linkage disequilibrium analyses which support a co-localization of PSORS4 and ATOD2 loci on human chromosome 1q21 and provided for the first time the evidence of an involvement of the LOR [9] gene in the pathogenesis of both disorders.…”
supporting
confidence: 53%
“…These two disorders are polygenic and reactive to psychosocial stressors. Susceptibility to psoriasis has been associated to the area of chromosome 1q21 (PSORS4) that encodes PSMB4, 30 and susceptibility to asthma and nasal polyps (O(MIM) MIM 208550) 14 has been associated with functional promoter SNPs in TBX21 (À1993T/C), in chromosome 17q21.3.…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping of SNPs was performed using a SEQUENOM MassARRAY MALDI-TOF mass spectrometer (Sequenom, San Diego, CA, USA) for analysis of unlabeled single-base extension minisequencing reactions 27 or using the Golden Gate assay (Illumina, San Diego, CA, USA) as part of a multiplex reaction as previously described. 26 Our SEQUENOM protocol implemented the very short extension method proposed by Sun and colleagues 30 whereby sequencing products are extended by only one base for three of the four nucleotides (due to the presence of dideoxynucleotides for three of the four nucleotides in the minisequencing reaction) and by several additional bases for the fourth nucleotide (specified in advance so as to represent one of the two alleles at a given SNP locus). This allowed for clearly delineated mass separation of the two allelic variants at a given locus.…”
Section: Methodsmentioning
confidence: 99%
“…The EDC includes members of S100 and small proline-rich region (SPRR) gene clusters and cornified envelope genes known to be structurally related to SPRR or S100 genes, including filaggrin, trichohyalin, loricrin and involucrin. Among these genes, loricrin[26], S100A2 [27] and S100A7 [28] are excluded as candidates for the PSORS4 locus. A recent study revealed that the association of psoriasis to the PGLYRP and SPRR genes at the PSORS4 locus on 1q21 shows heterogeneity among Finnish, Swedish and Irish families [29].…”
Section: Discussionmentioning
confidence: 99%